Pemberdayaan Anak Desa Melalui Groupwork di Masa Pandemi - Siti Aisyah; Husni Thamrin (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
The tutoring program is a form of community service program in 2021 which aims to grow the ability of early childhood children to interest in learning homes. In addition, there is another goal, namely from the implementation of this program for students to be able to apply the knowledge and theory that has been obtained from the world of lectures in addition to the campus being able to show the public that students are able to emphasize the existence of universities that are able to create or produce future cadres of the nation who are capable of bring about change for the better in society. The target of this service is children in Maimun Saleh Village, Sukajaya District, Sabang City Regency. This program has the main goal, namely through the tutoring program, early childhood children can gain basic knowledge of reading and arithmetic such as how to calculate properly and correctly. This tutoring program lasts about 3 months, each meeting 3 times a week. From this program, it can be seen that before this activity the children were not fluent in reading, writing and counting. After this activity the children had very good reading, writing and counting skills.